OBTAINING A NEW DEFOLATING COMPOSITION WITH PHYSIOLOGICAL ACTIVITY - Ergashev Dilmurod Adiljonovich; Khamdamova Shokhida Sherzodovna (Research Parks Publishers, 2021)
This article presents research on the development of a basic technological scheme for obtaining a defoliant with physiologically active additives in order to improve the quality. Studied the composition-properties of the diagram with the participation of chlorates and chlorides of calcium and magnesium, carbamide, ethanol and monoethanolammonium acetate. Revealed optimal rheological and agrochemical properties of solutions. A process flow diagram has been developed for obtaining a new complex acting defoliant